CHANGES IN THE REPLENISHMENT EDUCATION SYSTEM OF THE HANDBALL SPORT IN HUNGARY - Bernadett Juhász; Éva Bácsné Bába (University of Debrecen, Institute of Sport Sciences, 2021)
Development of talents care systems plays an important role in handball today. The goal of the Hungarian Handball Association is to ensure that all children of the same age receive the same training throughout the country. The Association recently introduced a standard feed-back education system. The aim of this research was to demonstrate the evolution of the talent care system, especially the innovations introduced by the Association. The research method was interviewing handball experts. Five experts answered our questions, former elite players, currently coaches. Based on their responses, it was possible to compare the old and the current status of the training programmes. We may conclude, that the structure of handball training has significantly developed both technically and tactically. Professionals agree, that there are a number of changes have occurred in the theory and methodology of handball. The newly introduced regional, electronic control system - described in the Age Handbook were considered to be useful by the interviewees. According to the results of our pilot study, the new unified educational training system may result in a more successful international presence in the long term.